UJI TOKSISITAS AKUT LIMBAH CAIR INDUSTRI TAHU TERHADAP IKAN BAWAL AIR TAWAR (Colossoma macropomum) (Acute Toxicity Test of Tofu Industrial Wastewater for Freshwater Pomfret (Colossoma macropomum) - Mars Sella Sinurat; Hesti Wahyuningsih; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Changes of chemical and physical parameters of water will disrupt theorganisms live in it, one of the types of organisms is freshwater pomfret (Colossomamacropomum). Toxicity tests are used to determine the status of tofu industrialwastewater for the mortality rate of freshwater pomfret. Therefore, the required value ofLethal Concentration 50% (LC50) 96 hours which is the concentration that causes 50%of test animals died within 96 hours of exposure time. This study aims to determine theLC50 value of tofu industrial wastewater for the freshwater pomfret and theconcentration effect of tofu industrial wastewater for the mortality rate of freshwaterpomfret. The study was conducted from July until August 2015. Research proceduresinclude preliminary testing, toxicity testing, and probit analysis. Toxicity testing of tofuindustrial wastewater showed the mortality rate of freshwater pomfret in treatmentconcentration. Treatment concentration 1,31% kill 20% of the fish, 1,72% kill 36,67%of the fish, 2,26% kill 53,33% of the fish, and 2,97 % kill 83,33% of the fish. Theresults showed that LC50 value for 96 hours of tofu industrial wastewater to thefreshwater pomfret is 20575,049 ppm (2,05%).Keywords : Freshwater Pomfret, Tofu Industry, LC50, Wastewater